2007
DOI: 10.1590/s0004-282x2007000500008
|View full text |Cite
|
Sign up to set email alerts
|

Cooling modifies mixed median and ulnar palmar studies in carpal tunnel syndrome

Abstract: -Temperature is an important and common variable that modifies nerve conduction study parameters in practice. Here we compare the effect of cooling on the mixed palmar median to ulnar negative peak-latency difference (PMU) in electrodiagnosis of carpal tunnel syndrome (CTS). Controls were 22 subjects (19 women, mean age 42.1 years, 44 hands). Patients were diagnosed with mild symptomatic CTS (25 women, mean age 46.6 years, 34 hands). PMU was obtained at the usual temperature, >32°C, and after wrist/hand coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another study showed that working in a cold environment had a higher odds ratio (OR) for developing CTS (OR 3.52, 95% CI 1.08–11.47) than working with repeated movements of the wrist (OR 2.15, 95% CI 1.14–4.07) [ 31 ]. Araujo et al also reported that after immersion in ice water, CTS patients had a more significant change in distal sensory latency of the median nerve than healthy subjects, which implied that CTS patients are more sensitive to cold exposure and tend to have Raynaud’s phenomenon [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that working in a cold environment had a higher odds ratio (OR) for developing CTS (OR 3.52, 95% CI 1.08–11.47) than working with repeated movements of the wrist (OR 2.15, 95% CI 1.14–4.07) [ 31 ]. Araujo et al also reported that after immersion in ice water, CTS patients had a more significant change in distal sensory latency of the median nerve than healthy subjects, which implied that CTS patients are more sensitive to cold exposure and tend to have Raynaud’s phenomenon [ 32 ].…”
Section: Discussionmentioning
confidence: 99%